1992
DOI: 10.1111/j.1365-3083.1992.tb02878.x
|View full text |Cite
|
Sign up to set email alerts
|

Immune Responses During Human Schistosomiasis Mansoni. XVIII. Immunologic Status of Pregnant Women and Their Neonates

Abstract: The immune status of peripheral blood mononuclear cells (PBMC) and sera of pregnant women infected with the helminth Schistosoma mansoni was studied during pregnancy and the cord blood mononuclear cells (CBMC) and sera from their offspring were studied at parturition. PBMC pokeweed mitogen-induced responses were maintained in gravid women, but the responses to both schistosome and non-schistosome antigenic preparations declined progressively during pregnancy. Schistosomal antigens stimulated proliferative resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 41 publications
2
44
1
Order By: Relevance
“…Most humans exposed to schistosomiasis are born to mothers who are or have been infected. There are ample reasons to think that in utero exposure to schistosome antigens or to idiotypic or anti-idiotypic antibodies may modify the response to subsequent infection in humans (Eloi-Santos et al 1989, Novato-Silva et al 1992) and in mice (Montesano et. al.…”
Section: General Considerations In the Interpretation Of Models Of Scmentioning
confidence: 99%
“…Most humans exposed to schistosomiasis are born to mothers who are or have been infected. There are ample reasons to think that in utero exposure to schistosome antigens or to idiotypic or anti-idiotypic antibodies may modify the response to subsequent infection in humans (Eloi-Santos et al 1989, Novato-Silva et al 1992) and in mice (Montesano et. al.…”
Section: General Considerations In the Interpretation Of Models Of Scmentioning
confidence: 99%
“…13 Exposure to maternal antigens might predispose a child to develop an immunoregulated, asymptomatic clinical presentation of the infection, and may predispose them to respond with an altered, perhaps more immunoregulated, form of schistosomiasis. 4,5,14 The probably immunogenic effects of such antigens as vaccines among infected mothers and the proper time to vaccinate newborns need to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…3 Exposure to maternal schistosome antigens might also predispose a child to respond with an altered, perhaps more immunoregulated form of schistosomiasis. 4,5 Thus, defining the extent to which maternal schistosome antigens may or not interfere with responses to new infant vaccines requires a better understanding of its main determinants.…”
Section: Introductionmentioning
confidence: 99%
“…King and others 3 reported that in vitro filarial and/or schistosome antigen-driven IgE production was more likely to be seen in newborns of schistosome-infected or filaria-infected mothers than in offspring of uninfected mothers. Other studies also showed enhanced levels of schistosome-specific antibodies in cord blood 14,[17][18][19] but did not discriminate between children of infected and uninfected mothers, 18 did not state whether an admixture of maternal to the fetal blood was excluded, 14,[17][18][19] or did not differentiate between the distinct antibodysubtypes. 14,17,19 Therefore, it is possible that the latter studies detected maternal IgG that crossed the placental barrier.…”
Section: Introductionmentioning
confidence: 99%